Healthcare professionals’ experiences and attitudes to care coordination across health sectors: an interview study - Maiken Hjuler Persson; Jens Søndergaard; Christian Backer Mogensen; Helene Skjøt-Arkil; Pernille Tanggaard Andersen (BMC Geriatrics, 2022)
Abstract Background The number of older people is increasing, resulting in more people endure chronic diseases, multimorbidities and complex care needs. Insufficient care coordination across healthcare sectors has negative consequences for health outcomes, costs and patient evaluation. Despite introducing initiatives to solve coordination challenges within healthcare, the need remains for more consistent solutions. In particular, improved care coordination would benefit older adults characterised by complex care needs, high use of healthcare resources and multiple care providers. Aims and objectives To identify and analyse healthcare professionals’ perspectives and approaches to care coordination across sectors when older people are acutely hospitalised. Design Qualitative interview study. Methods Semi-structured, individual interviews with 13 healthcare professionals across health sectors and professions were conducted. The strategy for the qualitative analysis was inspired by Kirsti Malterud and labelled ‘systematic text condensation’. This strategy is a descriptive and explorative method for thematic cross-case analysis of qualitative data. Results Four themes/categories emerged from the analysis; “Organisational factors”, “Approaches to care”, “Communication and knowledge”, and “Relations”. Conclusion Different organisational cultures can discourage intersectoral care coordination. Approaches to care vary at all levels across health sectors and professions. Organisational, leadership and professional identity affect the working cultures and must be considered in the future recruitment and socialisation of healthcare staff. Our research suggests that combinations of healthcare standardisations and flexible, adaptive solutions are required to improve intersectoral care coordination.